Psychometric validation of the Dysphagia Symptom Questionnaire in patients with eosinophilic esophagitis treated with budesonide oral suspension - Stacie Hudgens; Christopher Evans; Elaine Phillips; Malcolm Hill (SpringerOpen, 2017)
Abstract Background Eosinophilic esophagitis (EoE) is characterized by high levels of eosinophils in the esophageal mucosa. Patients with the disease present with a range of symptoms, including dysphagia (difficulty swallowing). The aim of this analysis was to assess the psychometric properties of the Dysphagia Symptom Questionnaire (DSQ), a patient-reported outcome (PRO) measure of dysphagia associated with EoE. Psychometric properties of the DSQ were assessed using data collected from a 12-week, phase 2, multicenter, randomized, double-blind, placebo-controlled trial of budesonide oral suspension in adolescents and adults (11-40 years old) with EoE. Results The study population comprised 93 patients with EoE; 94.6% of whom were white, 68.8% were male and the mean age (standard deviation) was 21.6 (7.7) years. Patients had been diagnosed with EoE for a mean of 37.6 months before study initiation. The DSQ was feasible to implement with few item-level data missing at baseline. Item discrimination was high, with floor and ceiling effects below the predefined threshold (≤9%). Higher DSQ scores corresponded with presence and increased severity of dysphagia, indicative of strong item discrimination among patients at baseline (threshold >50%). The DSQ was able to detect changes in symptoms over time and produced similar outcomes to those from physician- and other patient-rated measures, supportive of construct validity. The DSQ had strong test-retest reliability (intraclass correlation coefficient, r = 0.82); and was also responsive to disease-level changes, with higher DSQ scores corresponding to increased esophageal eosinophilic burden. Lastly, the percentage changes in the minimal clinically important difference and clinically important difference in DSQ score were estimated at −27.4% and −55.4%, respectively. Conclusions These analyses support the DSQ as a valid and reliable measure of dysphagia in patients with EoE. Changes in DSQ scores suggest a level of agreement between clinician, patient and histologic response. The DSQ should therefore be considered a viable PRO measure of dysphagia for use in future therapeutic studies of EoE.